Another excuse to trash newsrooms. - Kirtley, Jane (American Journalism Review)
Focuses on Senator Orrin Hatch's call for a legislation that will address the use of computer technology to create child pornography. Features of Hatch's bill; Threat to press freedom; Features of the Privacy Protection Act.